Effect of Electrode Product Merk with AWS E6013 JIS 4313 Specification on Low Carbon Steel in Weld Metal Area - Hafni Hafni (Jurnal Teknik Mesin, 2021)
In this study, the material used is low carbon steel with a tensile stress of 37kg/mm2, using electrodes with specifications AWS E 6013 JIS E 4313 with a diameter of 2.6 mm, which has a tensile stress of 60,000 psi or 43 kg/mm2. In the selection of specifications, what attracts attention is the price of these electrodes varies greatly with very different price differences. There is an assumption that cheap electrodes are of poorer quality than expensive ones. In this study, 3 different brands of electrode products were used with the AWS E 6013 JIS 4313 electrode specifications. SMAW welding process on low-voltage carbon steel material test material 37 kg/mm2 thickness 10, length 150 mm width 100 mm, using electrodes with AWS E 6013 JIS 4313 diameter 3.2 mm, electrode temperature 150 0F (65.5 0C), Welding position 1 G, groove connection type V, welding machine DC polarity DCRP current, voltage 23 volts, current 75 A on layer 1, 90 A on layer 2 and 85 A on layer 3, welding speed 32 cm/minute From the results of metallography testing in the weld metal area, it shows that the 3 brands of electrode products show the same composition of the market, namely ferrite pearlite with a ferrite matrix. From this it can be concluded that the price of the electrode product with specifications aws 6013 JIS 4313, does not affect the welding results.